Sistem 3 Strata sebagai Strategi Pemulihan dan Peningkatan Mutu Genetis Kambing dan Domba Indonesia (ULASAN) - T R Wiradarya (Faculty of Animal Science, Bogor Agricultural University, 2005)
modification of conventional production system called Pyramidal Structure is presented and termed as a Sistem 3 Strata. The system consists of 3 sub systems, they are Breeding, Multiplication, and Commercial. The Pyramidal system had been proven to be very effective in sustaining and improving the genetic potency of layers and broilers (poultry). The system was proposed to be implemented in sustaining and improving the genetic potency of the Indonesian sheep and goats. A simulation was conducted to evaluate the economic feasibility of the system using Garut sheep, based on the assumption of the 15% bank rate, at the capital investment level of Rp 6.400.000.000,00 and the production level of 155 lambs marketed per week. The results indicated that the economic feasibility was reached at the farm capacity of 8.537 su (Sheep Unit). The pay back period was 3,95 years, and the IRR and the NPV (i=20%) at the end of the 6th year were 19,17% and Rp 5.383.297.270,00. Key words: pyramidal structure, breeding, multiplication, commercial, Garut sheep